A systematic procedure to optimize Integrated Solar Combined Cycle power plants (ISCCs). (25th May 2018) - Mabrouk, M.T.; Kheiri, A.; Feidt, M.
Highlights: Integration of PTC in a conventional combined cycle is studied. A general layout and global optimization algorithm to find the best configuration. Solar efficiency is high for low solar shares and drops when this share increases. A maximal solar efficiency can be reached by increasing the solar mass flow rate. The effect of vacuum in the collectors and other parameters is investigated. Abstract: This study aims to find the optimal way to integrate a parabolic trough solar field into a gas fired combined cycle. The combined cycle studied here is composed of a gas turbine and a triple pressure bottoming Rankine cycle. A general layout is proposed and allows the integration of the solar source at all levels of temperature. A thermodynamic model is proposed to evaluate the performance of the system and then coupled to a constrained nonlinear optimization algorithm that uses a hybrid optimization technique combining Particle Swarm Optimization (PSO) and Gravitational Search Algorithm (GSA). This gives the optimal configuration of the heat exchanger networks used to harvest the solar source and the exhaust gases of the gas turbine. The effect of the system's main parameters on the solar integration performance was investigated such as the amount of the solar heat rate injected to the bottoming cycle, the mass flow rate of the solar source, the inlet temperature of the solar source and the outlet temperatures of the high pressure super-heater n°1 and the re-heater n°1. The approach used here is general and gives finally the real potential of the integration of a parabolic trough solar field into a combined cycle.